Trisomy 21 and Ebstein Anomaly: Diagnosis and Prognosis of a Rare Association - Brandão, Gabriela Rangel; Welter, Amanda Thum; Abech, Gabriel Dotta; Almeida, Carla Bastos da Costa; Okabayashi, Caio Seiti Mestre; Gadelha, Kerolainy Alves; Zen, Paulo Ricardo Gazzola; Rosa, Rafael Fabiano Machado (Journal of Pediatric Genetics, 2020)
Trisomy 21 is considered the most common chromosomal aneuploidy, and congenital heart disease (CHD) is highly prevalent and relevant to the morbidity and mortality of these patients. Ebstein anomaly (EA) is a rare CHD characterized by tricuspid valve dysplasia with inferior septal leaflet displacement. Herein, we described a patient with trisomy 21 who presented with EA and discuss the association between the two conditions based on a literature review. We conclude that the concomitant occurrence of both conditions is considered to be rare. These individuals are most frequently diagnosed during birth and childhood, and they usually have a good prognosis, as observed with our patient and is typical for EA patients in general. However, it is important to be aware that electrophysiologic anomalies may also be present.
Keywords: trisomy 21; congenital heart disease; Ebstein anomaly